Evaluation of Aspergillus niger as host for virus-like particle production, using the hepatitis B surface antigen as a model. - Plüddemann, A; Van Zyl, W (2003)
The filamentous fungus Aspergillus niger was transformed with the hepatitis B virus S gene encoding the major viral envelope protein under control of the constitutive A. nidulans glyceraldehyde-3-phosphate dehydrogenase ( gpdA) promoter. Approximately seven copies of the expression cassette were integrated on the genome, resulting in high-level transcription of the S gene. Production of the 24-kDa S protein and a 48-kDa S protein dimer in the membrane-associated protein fraction of the recombinant A. niger strain was shown through Western analysis. Electron microscopy of partially purified recombinant S protein revealed the formation of spherical pseudoviral particles with a diameter of 22 nm. The production level of hepatitis B pseudoviral particles was estimated to be 0.4 mg/l culture, which compares favourably with the reported levels initially obtained in yeast, indicating the potential of the Aspergillus expression system as an alternative, cost-effective vaccine production system.